Characterization of Thorium-bearing Minerals Using Micro-XRF in Metamorphic Rocks of Harau, West Sumatera - Tyto Baskara Adimedha; Heri Syaeful; Frederikus Dian Indrastomo; Ngadenin Ngadenin; Windi Anarta Draniswari (Indonesian Institute of Sciences, 2022)
In 1974, BATAN conducted a survey to review the potential of radioactive minerals in Harau, West Sumatra. The survey shows that there are radiometric anomalies in several locations in the area. However, the survey has not been able to show the radioactive elements and minerals found in Harau. This study aims to identify and characterize radioactive elements and minerals in Harau. To prove that detailed geological mapping, radiometric mapping with Gamma Spectrometer RS-125, and analysis using Micro-XRF